The Impact of Socioeconomic Status on the Subjective Well-Being of Indonesian Households - Moh. Athoillah; Nailul Alvi Muharromah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2024)
Subjective well-being (SWB) refers to people who have a positive emotion, high life satisfaction, and low negative sentiments. The socioeconomic condition of households plays a very important role in determining the level of SWB. Apart from economic factors, it is believed that there are some other factors affecting SWB of household. This research examines how socio-economic factors can affect SWB households using the Indonesia Family Life Survey (IFLS-5) microdata, this research will analyse both descriptive and inferential statistics. Applying descriptive analysis, we found that the number of happier households were much higher than those that were not. While, the logistic regression showed that economic status, education, health, marital status and stated feeling significantly affect to SWB. The study found no association among SWB, the number of dependents, and location of respondents. These findings showed that economic factors did not solely determine household welfare.